Clinical and demographical features, function of thyroid and autoantibodies in patients with vitiligo in Sanliurfa region - Dertlioğlu, Selma Bakar; Çiçek, Demet; Yeşilova, Yavuz; Demir, Betül; Uçak, Haydar (Harran Üniversitesi, 2013)
Background: Vitiligo, a depigmantasyon disorder, affects skin, hair and mucosal membranes. In this study, we aimed to investigate the relationship between the demographic, clinical features of vitiligo patients and autoimmune thyroid diseases in Sanliurfa region.Methods: From 2010 to 2012, we prospectively analyzed 254 vitiligo patients in the Department of Dermatology. The patients were diagnose after clinical and Wood's light examination. Patients' age, gender, age of onset, localization of lesions, initial location of lesions, involvement form of disease, family history of disease were recorded. Patients' and 100 healthy controls' serum free triiodothyronine FT3 , free thyroxine FT4 , thyroid stimulating hormone TSH , antithyroglobulin antibody anti-TG and antithyroid peroxidase antibodies anti-TPO were measured.Results: Two hundred and fifty four [123 male 48.4% and 131 women 51.6% ] of 11,007 patients in the clinic of Dermatology were diagnosed vitiligo. The mean age for women was 22.54±13.8 years, for men 25.32±15.3 years. Mean age of onset of disease for women was 16.58±10.37 and for men 18.45±11.08 years. Compared to control group, there was a statistically significant difference between the levels of serum FT4, TSH, anti-TPO and anti-TG in patients with vitiligo p=0.04, p

Amaç: Vitiligo deri, saç ve mukozal membranları etkileyen bir depigmantasyon bozukluğudur. Çalışmamızda Şanlıurfa bölgesindeki vitiligolu hastaların demografik, klinik özellikleri ve otoimmün tiroid hastalıkları ile ilişkisinin irdelenmesi amaçlanmıştır. Materyal ve metod: Bu çalışmada 2010-2012 yılları arasında polikliniğimize başvuran, klinik muayene ve Wood ışığı incelemesi sonucunda vitiligo tanısı almış 254 hasta prospektif olarak değerlendirildi. Olguların yaş, cinsiyet, hastalığın başlangıç yaşı, lezyonların yerleşim yeri, lezyonların başlangıç bölgesi, hastalığın tutulum şekli, hastalığın aile öyküsü kaydedilerek, hastaların ve 100 sağlıklı kontrolün serum serbest triiodotironin sT3 , serbest tiroksin sT4 , tiroid stimüle edici hormon TSH , antitiroglobulin antikor antiTG ve antitiroidperoksidaz antikor anti-TPO düzeyleri ölçüldü. Bulgular: Dermatoloji polikliniğine başvuran 11.007 hastaların 254'ünü %2.31 vitiligo hastaları oluşturmakta idi. İncelenen 254 hastanın, 123'ü erkek %48.4 ve 131'i kadın %51.6 idi. Ortalama yaş kadınlarda 22.54±13.8, erkeklerde 25.32±15.3 yıl olup hastalığın ortalama başlangıç yaşı kadınlarda 16.58±10.37, erkeklerde ise 18.45±11.08 yıl idi. Vitiligolu hastalar ile kontrol grubunun serum sT4, TSH, anti-TPO ve anti-TG düzeyleri arasında istatistiksel olarak anlamlı farklılık saptandı p=0.04, p
Şanlıurfa yöresinde vitiligo hastalarının klinik, demografik özellikleri, tiroid fonksiyonları ve otoantikorları Türkçe
Keywords: Clinical Sciences; Klinik Tıp Bilimleri